The effect of treatment of barley grain and malt with low-temperature plasma discharge on the malt gushing potential - Sylvie Běláková (Kvasný průmysl, 2018)
In 2015, the effect of treatment of spring barley grain and malt produced from it with low-temperature plasma discharge on the malt gushing potential was studied. Malting barley and malt produced from it were plasma-treated. In the malt samples, the gushing potential was determined. Simultaneously, selected quality parameters were assessed in the malt samples (Kolbach index, diastatic power, β-glucan content in wort, final attenuation, extract of malt in dry matter, relative extract at 45 °C, and friability). Gushing declined in the plasma-treated samples of malting barley or malt. The malt quality parameters remained unchanged.